Identifying and critically examining government legislation relevant to children's dental caries in Calgary, Alberta, Canada: a health inequities lens. (21st January 2019) - Weijs, Cynthia; Gobrail, Sara; Lucas, Jack; Zwicker, Jennifer; McLaren, Lindsay
Abstract: Objectives: Children's dental caries is an important and urgent public health concern that is largely preventable. Using a social equity framework, our objectives were to identify and critically examine government legislation relevant to the issue of children's dental health in Calgary, Alberta, Canada. Methods: We conducted a systematic, gray literature search of federal, provincial (Alberta), and municipal (Calgary) statutes and bylaws related to children's dental caries, through the relevant law databases. Eligibility criteria were applied for document screening and selection. Data extraction and synthesis pertained to objectives of the legislation (policy task), relevant agent or actor (level of government), and upstream or downstream focus, in terms of potential impact on social inequities in health. Results: Legislation ( n = 114) was retrieved and grouped into eight policy tasks. Most legislation fit under the policy tasks: protection of public safety and health promotion ( n = 40) and benefits and compensation ( n = 27). Federal and provincial governments have greater involvement in children's dental caries than municipal (Calgary) government. The majority of legislation was classified as upstream in orientation (e.g., improving living and working conditions; macro‐level policies). Conclusions: Analysis of legislation relevant to children's dental caries reveals policies that are more often upstream in nature, and unsurprisingly are multijurisdictional. Despite this, there remains a high prevalence and inequitable distribution of children's dental caries in Canada. This suggests that the nature of upstream involvement and fragmented government involvement is ineffective in tackling this pervasive and urgent public health issue. Implications for children's dental health are discussed.